2016
DOI: 10.1080/21573727.2016.1269005
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing practices in project-based design: tracing connections through cascades of visual representations

Abstract: Project-based design involves a variety of visual representations, which are evolved to make decisions and accomplish project objectives. Yet, such mediated and distributed ways of working are difficult to capture through ethnographies that examine situated design. A novel approach is developed that follows cascades of visual representations, and this is illustrated through two empirical studies. In the first case, Heathrow Terminal 5, analysis starts from paper-and modelwork used to develop design, tracing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 54 publications
(69 reference statements)
2
23
0
Order By: Relevance
“…As the study shows, and also Whyte et al [7] means, that total interaction and photorealism is not always necessary to make decisions through the process. The detail level should instead be adjusted according to the situation in which the IVE prototype is used.…”
Section: Analysis and Discussion Of The Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…As the study shows, and also Whyte et al [7] means, that total interaction and photorealism is not always necessary to make decisions through the process. The detail level should instead be adjusted according to the situation in which the IVE prototype is used.…”
Section: Analysis and Discussion Of The Resultsmentioning
confidence: 55%
“…Using game technology in virtual environments has the potential as a communication tool for architects to customers to understand the house-building process [3][4][5][6]. By providing virtual models across extended supply chain representations Whyte et al [7] argue that combined visualisations are evolved through practices in reified and hybrid forms in fabrication, assembly and on-site work. Industrialised house-builders has developed their information flow using drawings and instructions in documents.…”
Section: Introductionmentioning
confidence: 99%
“…Information traceability: ability to track decisions throughout the project process (Whyte et al 2016). A systematic approach to track and store information can potentially allow a faster feedback of changes during the process.…”
Section: Enable Communication Andmentioning
confidence: 99%
“…However, such activities can be difficult to track in design projects due to the distributed way of working in the construction industry. An attempt to better track the designers' interactions with their design was proposed by Whyte et al (2016). The authors suggested that the connections between different design representations (e.g.…”
Section: Bim-tool Use In Practice and Ways Of Analyzing Itmentioning
confidence: 99%
“…This critique is extended in other research such as Harty and Whyte (2009), Neff et al (2010) and Kokkonen and Alin (2016) who also call for qualitative research to complement the normative studies of BIM practices. Other studies have already contributed to improving the understanding of how BIM is used in practice, each focusing on individual aspects of using BIM, for example; representation (Bouchlaghem et al 2005, Whyte et al 2016, collaboration (Kerosuo et al 2013, Kokkonen and Alin 2016, Poirier et al 2016, interaction (Oxman 2006) and decision-making (Schade et al 2011). However, there are only a few studies that attempt to provide an in-depth and holistic analysis of how BIM is used in the design process.…”
Section: Introductionmentioning
confidence: 99%